JIGAR MEMBRANASIGA BOG’LIQ BO’LGAN Mg2+- ATFaza FERMENTLAR FAOLLIGIGA PESTITSID KARATENING TA’SIRI - Isabekova, M.A. (Actual problems and prospects of the study of the fauna, 2024)
Glutathioneductase, an important component of the antioxidant system of liver cells, is responsible for providing normal amounts of reversible glutathione in liver cells, the function of which is to keep most enzymes in active conformation. Most of it is in reversible state and is important in inactivating reactive toxic products.